Tripartite motif containing 25 promotes proliferation and invasion of colorectal cancer cells through TGF-β signaling. Issue 4 (12th July 2017) - Sun, Nianfeng; Xue, Yu; Dai, Ting; Li, Xiding; Zheng, Nanxiang
Abstract : Tripartite motif containing 25 (TRIM25) is a member of TRIM proteins and functions as an E3 (ubiquitin ligase). It has been found to act as an oncogene in gastric cancer cells and is abnormally expressed in cancers in female reproductive system. Here, we investigated the function of TRIM25 in colorectal cancer. TRIM25 was found to be significantly up-regulated in colorectal cancer tissues and cancer cell lines through real-time PCR assay. Colorectal cancer cells (CRCs) overexpressing TRIM25 exhibited a two-fold higher proliferation and migration rate compared with their parental lines in vitro . Moreover, TRIM25 also promoted tumor progression in vivo . Further study indicated that TRIM25 worked through positively regulating transforming growth factor β (TGF-β) signaling pathway to regulate the proliferation and invasion of CRCs. In summary, our results indicate that TRIM25 also acts as an oncogene in colorectal cancer and it functions through TGF-β signaling pathway. Thus, TRIM25 represents potential targets for the treatment of colorectal cancer.